1999
DOI: 10.1136/jme.25.4.302
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Japanese physicians' attitudes towards the care of adult patients in persistent vegetative state.

Abstract: Objectives-Ethical issues have recently been raised regarding the appropriate care ofpatients in persistent vegetative state (PVS) in Japan. The purpose of our study is to study the attitudes and beliefs ofJapanese physicians who have experience caringfor patients in PVS. Design and setting-A postal questionnaire was sent to all 317 representative members of the J7apan Society ofApoplexy working at university hospitals or designated teaching hospitals by the Ministry of Health and Welfare. The questionnaire as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…This is a commonly observed phenomenon in other end-of-life situations such as the provision of basic needs to patients in the PVS. Asai et al (1990) found that fewer individuals would agree to withdraw artificial nutrition, hydration and antibiotics in the event of pneumonia developing in a stranger than in themselves (3% vs. 40% and 30% vs. 31%). The family decision-making about withdrawing life-support from a patient with BSD is complex and involves three interrelated processes (Swigart et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This is a commonly observed phenomenon in other end-of-life situations such as the provision of basic needs to patients in the PVS. Asai et al (1990) found that fewer individuals would agree to withdraw artificial nutrition, hydration and antibiotics in the event of pneumonia developing in a stranger than in themselves (3% vs. 40% and 30% vs. 31%). The family decision-making about withdrawing life-support from a patient with BSD is complex and involves three interrelated processes (Swigart et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…If the same patient developed pneumonia, only 4% would withhold AHN but 30% would withhold antibiotics. Interestingly, 40% of the practitioners responding to the survey would withhold AHN if they themselves were in PVS [Asai et al, 1999]. Lacking data on the reasons, the authors speculate that the dramatic difference between Japanese and American attitudes may be due to different religious views on the meaning of death, or of possibility of a patient with PVS sharing a meaningful life with friends and family [Asai et al, 1999].…”
Section: Withdrawing Artificial Hydration and Nutrition-a View Of Thementioning
confidence: 95%
“…Interestingly, 40% of the practitioners responding to the survey would withhold AHN if they themselves were in PVS [Asai et al, 1999]. Lacking data on the reasons, the authors speculate that the dramatic difference between Japanese and American attitudes may be due to different religious views on the meaning of death, or of possibility of a patient with PVS sharing a meaningful life with friends and family [Asai et al, 1999]. In an analysis of the Halacha (the Judaic legal-ethical system) and the ethics of limiting AHN in the elderly who are terminally ill, Schostak points out that the overall guiding principle is the sanctity of life and the subsequent obligation to restore health since the patient's body is the "property" of God.…”
Section: Withdrawing Artificial Hydration and Nutrition-a View Of Thementioning
confidence: 99%
“…Eine Umfrage unter japanischen Ärzten ergab, dass der Abbruch künstlicher Ernährung bei einem "apallischen Syndrom" auch im Fall einer vorauslaufenden Willenserklärung nur von 17 der Befragten befürwortet wurde und dass sie mehrheitlich unter den gleichen Umständen auch für sich selbst einen Nahrungsentzug ablehnten [3]. In unserem eigenen Kulturkreis gilt dagegen die Selbstbestimmung am Lebensende als ein hohes Gut und hat in der letzten Dekade stark an Bedeutung gewonnen [4].…”
Section: Ethische Implikationenunclassified